A deep conical agarose microwell array for adhesion independent three-dimensional cell culture and dynamic volume measurement. Issue 1 (6th December 2017) - Thomsen, Andreas R.; Aldrian, Christine; Bronsert, Peter; Thomann, Yi; Nanko, Norbert; Melin, Nicolas; Rücker, Gerta; Follo, Marie; Grosu, Anca L.; Niedermann, Gabriele; Layer, Paul G.; Heselich, Anja; et al.
Abstract : Miniaturised conical measures for cell aggregates. Abstract : Multicellular spheroids represent a well-established 3D model to study healthy and diseased cells in vitro . The use of conventional 3D cell culture platforms for the generation of multicellular spheroids is limited to cell types that easily self-assemble into spheroids because less adhesive cells fail to form stable aggregates. A high-precision micromoulding technique developed in our laboratory produces deep conical agarose microwell arrays that allow the cultivation of uniform multicellular aggregates, irrespective of the spheroid formation capacity of the cells. Such hydrogel arrays warrant a steady nutrient supply for several weeks, permit live volumetric measurements to monitor cell growth, enable immunohistochemical staining, fluorescence-based microscopy, and facilitate immediate harvesting of cell aggregates. This system also allows co-cultures of two distinct cell types either in direct cell–cell contact or at a distance as the hydrogel permits diffusion of soluble compounds. Notably, we show that co-culture of a breast cancer cell line with bone marrow stromal cells enhances 3D growth of the cancer cells in this system.